Common features of video games and social networks: importance for international taxation. (December 2020) - Vvedenskaya, Anna
Abstract : In the last decade, significant review and change have been done regarding the taxation of profits from multinational companies. The OECD BEPS Action 1 is focused on granting additional taxing rights to jurisdictions where the customers of the service are located. This is because consumers add to the value creation process (prosumers), together with the company itself. Many enterprises do not have a physical presence at market jurisdictions because of the worldwide digitalization of the business process. With distant sales, they avoid sufficient taxation at the source countries. Multiple jurisdictions, businesses, and individuals provided various taxing rights allocation proposals. OECD considered some of them as possible ways to address the issue of under-taxation at market jurisdiction. This article evaluates the applicability of the OECD analysis of the value creation to the video games industry under the angle of differences and similarities between single-player and multi-player video games with social networks. This work is focused on the differences related to user participation and network effects for the value creation process. It explores the importance of the user participation and network effects for the value creation process of single-player and multi-player video games, to find if that respective taxing rights allocation should be different for these types of video game. It also analyses main proposals on taxing rights allocation, their applicability to the industry, and if these proposals acknowledge the differences in value creation based on the network effects of the video game. It was found that the existing proposals are not always consistent with the preparatory work on value creation analysis performed by the OECD and do not consider the named differences. The results of this work support the position that the proposals, including the most recent one, meet the existing urge for the taxing rights reallocation, but are mainly politically-driven and not always in line with the existing principles of international tax law.